Evaluation of the antiviral and antimicrobial activities of triterpenes isolated from Euphorbia segetalis - Madureira, AM (2015)
A phytochemical reinvestigation of the whole plant of Euphorbia segetalis yielded five tetracyclic triterpenes: 3 beta- hydroxy- cycloart- 25- en- 24- one ( 1), cycloart- 25- ene- 3 beta, 24- diol ( 2), cycloart- 23- ene- 3 beta, 25- diol ( 3), lanosta-7,9( 11), 24- trien- 3 beta- ol ( 4) and lanosta- 7,9( 11), 24( 31)- trien- 3 beta- ol ( 5). 3 beta- acetoxy- cycloart- 25- en- 24- one ( 1a) and glutinol ( 6), lupenone ( 7), dammaranodienol ( 9), cycloartenol acetate ( 10), 24- methylenecycloartanol acetate ( 11) and beta- sitosterol ( 12), isolated previously, were evaluated for their antiviral activities against Herpes simplex virus ( HSV) and African swine fever virus ( ASFV). Lupenone exhibited strong viral plaque inhibitory effect against HSV- 1 and HSV- 2. The in vitro antifungal and antibacterial activities of 1a, cycloart- 23- ene- 3 beta, 25- diol, 3- acetate ( 3a) and 6 - 12 were also investigated.